Wild Plant-Based Functional Foods, Drugs, and Nutraceuticals - Pinela, José (2018)
Plants have been used as food and medicine since ancient times and their importance in today's society is unquestionable. Nowadays, many consumers recognize the relationship between nutrition and health, in relation to "functional foods" and "nutraceuticals." The global functional food and nutraceutical market is growing at a rate that is outpacing the traditional processed food market. In this chapter, we present some wild plants that are claimed to have functional properties. Novel applications and formulations of nutraceuticals are described, as are some products already available on the market. Furthermore, the relation between bioactive phytochemicals and active principles is explained, listing examples of wild plant-based drugs and the different therapeutic targets that can be explored for this type of therapy. The concepts of functional food, nutraceutical, and plant drug are clarified. Some opportunities and challenges motivating the development and regulation of these plant-based products are also discussed.